1997
DOI: 10.1515/jpme.1997.25.1.85
|View full text |Cite
|
Sign up to set email alerts
|

High-dose gammaglobulin (IVIG) followed by intrauterine transfusions (IUTs): a new alternative for the treatment of severe fetal hemolytic disease

Abstract: Intrauterine fetal transfusion is currently the therapy of choice in cases of severe anti-D isoimmunisation. However, its efficacy is reduced in patients with early severe hydrops fetalis due to the technical difficulties in performing this procedure before 20 weeks' gestation. The purpose of this study was to determine whether early onset of high-dose gammaglobulin therapy followed by intrauterine transfusions (IUTs) is more effective than IUTs alone in the treatment of very severe isoimmunised fetuses. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 7 publications
4
35
0
Order By: Relevance
“…In order to overcome the difficulty in accessing a small vessel measuring less than 3-5 mm in early gestation, treatment with plasmapheresis and IVIG, aiming to prolong gestation before the need for IUT, has been reported 18,19 . Ruma et al described nine patients with severe RBC alloimmunization, who were treated with combined plasmapheresis and IVIG, which deferred their first IUT to a mean gestational age of 24 weeks, when the procedure is easier to perform, resulting in the survival of all infants 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to overcome the difficulty in accessing a small vessel measuring less than 3-5 mm in early gestation, treatment with plasmapheresis and IVIG, aiming to prolong gestation before the need for IUT, has been reported 18,19 . Ruma et al described nine patients with severe RBC alloimmunization, who were treated with combined plasmapheresis and IVIG, which deferred their first IUT to a mean gestational age of 24 weeks, when the procedure is easier to perform, resulting in the survival of all infants 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Objective To determine perinatal outcome in pregnancies with early severe red blood cell (RBC) IUT was 20.4 (range,[16][17][18][19][20][21][22] weeks, and between one and nine transfusions were needed during pregnancy. Transfusion was via the intrahepatic vein (IHV) (n = 19), umbilical vein (n = 6) or umbilical artery (n = 2), or was intracardiac (n = 2) or intraperitoneal (n = 1).…”
Section: Introductionmentioning
confidence: 99%
“…In most fetal therapy centers applying IVIG, it is started at 400 mg/kg maternal weight/day for 5 consecutive days, repeated every 2-3 weeks [80,82,84,85]. An alternative regime could be 500 mg-1 g/kg maternal body weight weekly [78,86].…”
Section: Intravenous Immunoglobulins (Ivig)mentioning
confidence: 99%
“…Nevertheless, they concluded that for hydropic fetuses and for fetuses with advanced fetal anemia, IUT is inevitable [90]. In a retrospective study of the same group, patients receiving IVIG before 20 weeks had significantly less hydropic fetuses and a lower fetal mortality rate compared to patients treated with IUT alone [84]. However, in another small series of four cases of severe RhD-immunization, IVIG did not seem to have any effect on transfusion frequency, maternal antibody titers or hydrops [91].…”
Section: Intravenous Immunoglobulins (Ivig)mentioning
confidence: 99%
“…Margulies et al [43] conducted the largest prospective series to date in which 24 severely Rh-sensitized pregnant women were treated with IVIG alone until delivery and demonstrated that IVIG use should be initiated before 28 weeks or before the appearence of hydrops. In addition, Voto et al [85] demonstrated the predominance of the combined treatment with IVIG and IUT over IUT alone, as in the fi rst group, severe fetal anemia was less common and fetal mortality was reduced by 36 % compared with the second group. In the more recent case series, Fox et al [25] described the management of six pregnant women, with a previous pregnancy complicated by severe anemia before 20 weeks ' gestation, with intraperitoneal transfusion at 2-week intervals between 16 and 21 weeks and adjuvant maternal IVIG therapy.…”
Section: Intravenous Immunoglobulinmentioning
confidence: 99%